A waste to worth approach in preparing Ferric vanadate Nanoparticles using peel extract for photocatalytic dye degradation induced by UV light - Priya, R.; Stanly, S.; Anuradha, R.; Sagadevan, Suresh; Muthukrishnan, Lakshmipathy (Elsevier, 2019)
Photocatalytic decolorization of methylene blue dye (MB) under obvious light has been examined utilizing Ferric Vanadate nanoparticles (FV NPs). The photocatalyst was prepared by using various natural product peel waste (Pomegranate, Apple, Grapes, Orange and Banana (PAGOB)). The physico- and opto-chemical properties of prepared Ferric Vanadate nanoparticles (FV NPs) were determined using X-ray diffraction (XRD) and High-resolution Scanning Electron Microscope (HRSEM). UV–vis spectrophotometric analysis was used to study the rate of photocatalytic degradation of the dye measuring the optical density at regular time intervals. The factors influencing the photocatalytic degradation viz. effect of pH, the concentration of the dye, the quantity of photocatalyst (FV NPs) and the effect of light intensity on the rate of photocatalytic response was investigated under ideal conditions. The outcome demonstrates that degradation achieved 99% under ideal conditions. © 2019 Elsevier GmbH